Предмет: Математика,
автор: nikitavoronazp
Плмогите решить
11,4y+3,8y - 4,6y + 12,7 = 67,82.
Ответы
Автор ответа:
0
Ответ:
10.6у=67,82-12,7
10,6у=55,12
у=55,12/10,6
у=5,2
Автор ответа:
0
11,4y + 3,8y - 4,6y + 12,7 = 67,82
(11,4 + 3,8 - 4,6) * y = 67,82 - 12,7
10,6y = 55,12
y = 55,12 / 10,6
y = 5,2
проверка
11,4 * 5,2 + 3,8 * 5,2 - 4,6 * 5,2 + 12,7 = 67,82
67,82 = 67,82 -- верно
ответ: y = 5,2
Похожие вопросы
Предмет: Русский язык,
автор: 89037082329
Предмет: Английский язык,
автор: Алина7365
Предмет: Русский язык,
автор: yasinkaj16
Предмет: Английский язык,
автор: egorovan2
Предмет: Математика,
автор: ankazaim2277